Dear valued customer a descriptive study of the promotional strategies employed by MAKRO Warehouse Club - Fabella, Arla C.
This is a study of the promotional strategy of MAKRO Warehouse Club, Inc. and its employment of direct mail advertising. The study employed the content analysis in studying the contents of MAKRO'S direct mail. A survey was also conducted on the customers of MAKRO in order to determine their behavior, opinions and perceptions of the store and its advertising. Content analysis was applied in order to determine how MAKRO allotted its advertising space in its direct mail campaign. It was found that in all its direct mail issues, MAKRO prioritized full color photographs over text. Food items, represented in groups, were given more emphasis than non-food items. Bright and striking colors were used in the materials sent out to its customers, as well as good quality paper and printing. Textual content was kept to a minimum. Survey results point out that majority of MAKRO'S customer operate their own business and that they find advertising materials to be reliable, attractive, informative, and would, in all probability, convince them to purchase goods. Furthermore, it was found that the customers of MAKRO rely on the direct mail advertisements for information. Thus, for MAKRO'S type of business (wholesale), direct mail advertising proved to be effective in communicating with their customers.